Stimuli‐Responsive Deep‐Blue Organic Ultralong Phosphorescence with Lifetime over 5 s for Reversible Water‐Jet Anti‐Counterfeiting Printing. (24th June 2021) - Zhang, Jingyu; Xu, Shen; Wang, Zijie; Xue, Peiran; Wang, Wuji; Zhang, Longyan; Shi, Yuqi; Huang, Wei; Chen, Runfeng
Abstract: Organic ultralong room temperature phosphorescence (OURTP) materials with photophysical properties sensitive to external stimulus are highly attractive for advanced applications. However, most OURTP molecules are in crystal and OURTP materials with good practicability and stimulus‐responsive character are hard to be achieved. Here, we report, for the first time, the highly efficient, ultralong‐lived and deep‐blue OURTP materials by simply doping boron phosphor into cyanuric acid host. Host–guest OURTP composites with abundant and tunable H‐bond network are highly stable in air with ultralong lifetime of 5.08 s at room temperature. They are sensitive to water, which can strength the H‐bond network to significantly enhance OURTP quantum yield from 16.1 % to 37.6 %. Anti‐counterfeiting paper was easily prepared for water‐jet printing; the jet‐printed high‐resolution OURTP patterns can be easily erased by solvent fuming for another printing/erasing cycle with high reversibility. Abstract : Highly efficient organic ultralong room‐temperature phosphorescence (OURTP) materials responsive to water have been achieved, showing phosphorescent quantum yield of 16.1 % and lifetime of 5.08 s. Lifetime‐encrypted anti‐counterfeiting patterns are jet‐printed using water as ink on the water‐responsive OURTP paper and erased by solvent fuming with high reversibility and cycling stability.